Re‐evaluation of the Roseau Tuff eruptive sequence and other ignimbrites in Dominica, Lesser Antilles - TRACY M. HOWE; JAN M. LINDSAY; PHIL SHANE; AXEL K. SCHMITT; DANIEL F. STOCKLI (Journal of Quaternary Science, 2014)
The island of Dominica hosts several ignimbrites, including the Roseau Tuff, thought to represent the largest eruption in the Caribbean in the past 200 000 years. The volcanic stratigraphy of the island is poorly understood due to limited outcrops and a paucity of geochemical and geochronological data. The discovery of a new fully accessible exposure of three ignimbrites intercalated with paleosols provides an opportunity to re‐evaluate the current stratigraphic framework of ignimbrite‐forming eruptions on the island. Whole‐rock analyses of pumice clasts from Dominica ignimbrites are andesitic (61–66% SiO 2 ) and in most cases are geochemically indistinguishable. Ignimbrites in the north of the island have less evolved glass compositions (73–75% SiO 2 ) and more mafic orthopyroxene compositions (En > 56) than their southern counterparts (75–78% SiO 2 ; En